The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/pits.22228
|View full text |Cite
|
Sign up to set email alerts
|

School psychology graduate education retention research characteristics: Implications for diversity initiatives in the profession

Abstract: Lack of racial and ethnic diversity in the school psychology workforce has been a concern since the profession's inception. One solution is to graduate more racially and ethnically diverse individuals from school psychology programs. This structured review explored the characteristics of studies published from 1994 to 2017 that investigated graduate student retention and school psychology. An electronic search that included specified databases, subject terms, and study inclusion criteria along with a manual se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Despite a recent decline in the use of exclusionary discipline practices in U.S. schools (Musu et al, 2019), racially and ethnically minoritized (REM) (Proctor & Owens, 2019) youth remain disproportionately referred to the office (Anyon at al., 2018), suspended (Ksinan et al, 2019) and expelled (Bal et al, 2019). Black and Native American youth in particular are also more likely than their White peers to be identified to receive special education services for emotional disturbance (Bal et al, 2019; Donovan & Cross, 2002) and placed in more restrictive special education settings (Skiba et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a recent decline in the use of exclusionary discipline practices in U.S. schools (Musu et al, 2019), racially and ethnically minoritized (REM) (Proctor & Owens, 2019) youth remain disproportionately referred to the office (Anyon at al., 2018), suspended (Ksinan et al, 2019) and expelled (Bal et al, 2019). Black and Native American youth in particular are also more likely than their White peers to be identified to receive special education services for emotional disturbance (Bal et al, 2019; Donovan & Cross, 2002) and placed in more restrictive special education settings (Skiba et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are consistent with research suggesting that students with minoritized cultural identities may experience unique barriers or challenges in the course of their graduate preparation (e.g., Proctor and Truscott 2012 ) and reveal the need to target graduate school preparation and retention efforts. Proctor and Owens’ ( 2018 ) structured review on graduate school retention research in school psychology found only two studies that met their inclusion criteria, but both studies reported four shared retention strategies for students with minoritized cultural identities: (1) an inclusive program atmosphere, (2) access to diverse professional networks, (3) mentorship opportunities, and (4) program commitment to multicultural issues. The authors also recommended that programs conduct annual surveys with all students to assess retention-related issues (e.g., perceptions of belongingness, peer and faculty support) and meet with students with minoritized cultural identities to better understand their program-related experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this promise, little guidance exists about how to successfully implement DCs within programs. Further, given that the field of school psychology is very homogenous (Castillo et al, 2013), there is a critical need to advocate for institutional commitment to diversity, equity, and inclusion (DEI) issues and inclusive learning environments in these homogenous spaces of predominately White institutions (Proctor & Owens, 2019), where not only the majority of the student body is White, but also there are “embedded institutional practices that are based in whiteness” (Bourke, 2016; p. 20). Given the paucity of research in DC implementation, particularly within school psychology, we offer two case examples of the implementation of DCs in school psychology training programs at predominantly White institutions (PWI).…”
Section: Diversity Committeesmentioning
confidence: 99%